Who and how do participate strategic planning? - Viire Täks; Maaja Vadi (OrdnungsPolitisches Portal (OPO), 2019)
The paper offers new insights into how concurrent combinations of different strategic planning participants is related to the usage of various management tools in the company. It shares the light to two areas with little empirical studies - concurrent involvement of strategic planning participants and the relation between strategic planning participants and use of management tools. Through this, it helps to explain strategic planning participants influence strategy implementation processes. The study is based on a dataset of 204 Estonian companies. To analyse relationships Bayesian networks is chosen and the dynamic networks illustrate the findings. Using this analysing method allows evaluating probabilistic relations between various combinations of strategic planning participants and use of management tools. The study shows that leading actors of strategic planning are owners, top and middle managers. Middle managers have a central role in involving lower positions in the company to strategic planning. When owners are involved in strategic planning, companies tend to use externally oriented management tools like customer relationship management. Involvement of top managers is related to internally oriented management tools, most probably with business process re-engineering. In case of concurrent involvement of top managers and owners, owner-related management tools are preferable in use. Middle managers are most often involved in strategic planning when benchmarking and first-level managers when business process re-engineering is in use. Bayesian network models were also composed of the involvement of specialists and blue-collar workers, while these networks did not show any relationships between strategic planning participants and management tools.
Keywords: 330; strategic planning; strategic planning participants; management tools; Strategy implementation; Estonia; Bayesian networks